2017
DOI: 10.5005/jp-journals-10024-2025
|View full text |Cite
|
Sign up to set email alerts
|

Additive and reducing Effects between Calcium Hydroxide and Current Irrigation Solutions

Abstract: Introduction: Microorganisms should be considered to have the major role in starting and perpetuation of pulpo-periapical diseases. Using intracanal medicaments is necessary to gain a bacteria-free environment in the canal system. Calcium hydroxide (abbreviated as Ca(OH) 2), which is the most commonly used medicament in endodontic therapy, has been shown to be effective against primary sources of infection; however, its effectiveness against some microorganisms, such as Candida albicans and Enterococcus faecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…11 Results of a systemic review concluded that the major effects of steroids on pain reduction occur during 24-72 hours and this coincides with our study. 4 Another study by Mohammed Saadi Alarbeed et al, 14 comparing use of Calcium Hydroxide alone and in combination with chlorhexidine concluded that the mixture was more effective in reducing pain in necrotic teeth. The use of chlorhexidine as a potential intracanal medicament has proven to be effective because of its broad antimicrobial spectrum including enterococcus faecalis, and its ability to maintain its antibacterial action for a prolonged period of almost three months.…”
Section: Group-c (N=94) Dexamethasone Pvaluementioning
confidence: 99%
See 1 more Smart Citation
“…11 Results of a systemic review concluded that the major effects of steroids on pain reduction occur during 24-72 hours and this coincides with our study. 4 Another study by Mohammed Saadi Alarbeed et al, 14 comparing use of Calcium Hydroxide alone and in combination with chlorhexidine concluded that the mixture was more effective in reducing pain in necrotic teeth. The use of chlorhexidine as a potential intracanal medicament has proven to be effective because of its broad antimicrobial spectrum including enterococcus faecalis, and its ability to maintain its antibacterial action for a prolonged period of almost three months.…”
Section: Group-c (N=94) Dexamethasone Pvaluementioning
confidence: 99%
“…Different vehicles can be used for its delivery into the root canals including distilled water, normal saline, chlorhexidine and different corticosteroid solutions. 3,4 Several studies have reported using Calcium Hydroxide in combination with Chlorhexidine as an intracanal dressing for post treatment pain. Chlorhexidine is an antibacterial that is effective against many gram positive and negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Other biological effects attributed to CH include an anti-inflammatory and a pro-mineralizing potential [ 24 , 25 ]. Chlorhexidine (CHX) has also been proposed as an intracanal medication because of its strong antimicrobial properties and its affinity for dental tissues that allows for prolonged drug release [ 26 , 27 ]. Our group recently confirmed that a mixture of CH and CHX is effective against microorganisms such as E. faecalis , which is frequently considered as non-susceptible to CH alone [ 28 ].…”
Section: Introductionmentioning
confidence: 99%